Stabilizing the MXene by Ion Confinement Shielding in a Wide Temperature Range. Issue 2 (29th November 2022) - Zhang, Xuefeng; Liu, Xudong; Feng, Yufa; Qiu, Si; Lu, Ming; Bo, Peng; Liao, Qingyu; Liu, Yong; Li, Hao
Abstract : Herein, the environmental stability of MXenes aqueous solution in a wide temperature range is successfully enhanced by a mechanism of ion‐confined shielding. Combined with experiments and molecular dynamics simulation, it is found that, in an aqueous solution, a confinement shielding layer formed by the electrostatic adsorption of the introduced hydronium ion onto the electronegative surface of nanosheets, which efficiently constrains free water molecules near the nanosheet surface through hydration, and prevents nanosheets from an attack of water molecules and dissolved oxygen through its steric hindrance effect. Moreover, the hydronium ions could induce the aggregation of nanosheets and further reduce the active surface area of exposed Ti3 C2 T x . Under the aforementioned synergistic effect, the storage duration allowing Ti3 C2 T x aqueous solution to keep stable is extended to 100 days at 25 °C and 30 days at 60 °C, respectively. In addition, hydronium ion has the advantages of low cost, environmentally friendly, and easy recovery. It also shows an excellent protection effect at low concentration, such as 2 mol L −1 . The present study provides guidance for the prolongation of life of the MXenes device working under long‐term or high‐temperature aqueous conditions and the selection of electrolytes for supercapacitors. Abstract : The environmental stability of MXenes aqueous solution in a wide temperature range is successfully enhanced by a mechanism of ion‐confined shielding.